Influence of biosolids rate on chemical properties of an oxisol in São Paulo, Brazil - Cristina Alves, Marlene; Paz Gonzalez, Antonio; Colodro, Gilberto; Perecin Junior, Helio; Vidal Vazquez, Eva (Taylor & Francis Inc, 2006)
Organic residues may cause major health and environmental problems. This is the case in our study area, where more than 10 billion L per year of residential and industrial waste are produced. Land application of biosolids can be an economical solution by recycling waste and can provide valuable fertilizer if used correctly. The aim of this work was to study the effect of biosolids on the chemical properties of an Oxisol. The experiment was located at Ilha Solteira northwest of São Paulo State, Brazil. The soil was cropped to Sorghum bicolor.The field experimental design consisted of random blocks with six treatments and four replications of each treatment. Biosolids were surface applied to four treatments at rates of 5, 10, 20, and 40 Mg ha(-1) on a dry matter basis; in addition, a treatment with mineral fertilizer and a control were included. One year after biosolids application, soil samples were taken at 0-10, 10-20, and 20-40 cm. Organic matter content (Walkley-Black) and pH (CaCl2) were routinely determined. Cation exchange capacity, exchangeable bases (Ca, Mg, K), and P were determined by exchange resin extraction. No significant differences in any of the analyzed properties were found below the 20 cm depth. Extractable phosphorus (P) and potassium (K) increased with increasing biosolids rate in the top 20 cm, whereas calcium (Ca) and (Ma) magnesium content were not significantly influenced by biosolids. Soil pH decreased with increasing biosolids application. The sewage sludge application did not influence the sorghum production in the first year of culture, under unfavorable soil moisture conditions, but it influenced the dry matter.
Keywords: organic fertilization; sewage sludge; soil management; sorghum